L’allevamento bovino a stabulazione fissa: la nuova cascina. - Galli, Barbara (OS. Opificio della Storia, 2022)
The essay provides some notes on the formal and stylistic characteristics that characterize contemporary buildings for cattle rearing with fixed stabling. Starting from the structure of “cascine” we analyze the current status and the possible lines of development in the design of new structures and in the re-functionalization of pre-existing buildings.